The Importance of ICT Integration by Manufacturing Small and Medium Enterprises in Kwazulu-Natal, South Africa - Bingwa, Luyanda Loraine; Ngibe, Musawenkosi (Contemporary Issues of Business and Management: The Proceedings of the \(10^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
The rapid evolution of technology has sparked a debate across the globe concerning the need for Small and Medium-sized Enterprises (SMEs) to incorporate Information and Communication Technology (ICT) to maintain competitiveness and sustainability. However, South African manufacturing SMEs continue to face challenges that hinder their ability to utilise ICT. The identified gap highlights SMEs' failure to acknowledge, prioritise and capitalise on the significant skills that industry specialists provide while navigating the intricate challenges of ICT integration. The purpose of this paper is to explore and analyse the perspectives of IT (Information Technology) industry experts regarding the challenges and opportunities associated with ICT adoption by manufacturing SMEs in KwaZulu-Natal (KZN). Adopting an interpretive paradigm, the present qualitative inquiry interviewed ten IT industry specialists in KZN, which were identified through purposive sampling, to explore the understudied dynamics associated with ICT adoption by manufacturing SMEs. The study findings demonstrated a lack of support from IT professionals in assisting manufacturing SMEs with their technology-related difficulties, leading to limited resources, lack of expertise, and resistance to change. The study therefore recommends the development of industry-specific advisory boards that are designed to not only promote engagements among IT experts and manufacturing SME managers regarding ICT adoption challenges but to also share insights that will lead to enhanced SMEs' competitiveness and sustainability. In addition, it is recommended that the government should provide assistance programmes which include grants that manufacturing SMEs can utilise to conduct ICT pilot projects under the supervision of IT experts.